Recent advances in overexpression of functional recombinant lipases - Fatin Liyana Alias; Nima Ghahremani Nezhad; Yahaya M. Normi; Mohd Shukuri Mohamad Ali; Cahyo Budiman; Thean, Chor Leow (Springer Nature, 2023)
Heterologous functional expression of the recombinant lipases is typically a bottleneck due to the expression in the insoluble fraction as inclusion bodies (IBs) which are in inactive form. Due to the importance of lipases in various industrial applications, many investigations have been conducted to discover suitable approaches to obtain functional lipase or increase the expressed yield in the soluble fraction. The utilization of the appropriate prokaryotic and eukaryotic expression systems, along with the suitable vectors, promoters, and tags, has been recognized as a practical approach. One of the most powerful strategies to produce bioactive lipases is using the molecular chaperones co-expressed along with the target protein’s genes into the expression host to produce the lipase in soluble fraction as a bioactive form. The refolding of expressed lipase from IBs (inactive) is another practical strategy which is usually carried out through chemical and physical methods. Based on recent investigations, the current review simultaneously highlights strategies to express the bioactive lipases and recover the bioactive lipases from the IBs in insoluble form.